تقويم الأداء التدريسي للطلاب المعلمين المتخصصين في اللغة العربية بكلية التربية بجامعة أم القرى في ضوء المهارات التدريسية - الزهراني، مرضي بن غرم الله بن حسن (جامعة مؤتة, 2019)
The study aimed to evaluate the teaching performance of student of the teachers of the Arabic Language in the College of Education at Umm Al-Qura University in light of teaching skills. To attain this objective, the researcher employed the descriptive methodology, designed an observation card which comprised (58) items in four domains relating to planning the language lesson, its implementation and assessment; interaction and class management; the card's validity and reliability had been measured, and then administered to a random sample of (30) student teachers specializing in the Arabic Language and enrolled in the educational preparation program, College of Education, in the academic year 1438H/2017M. The study results revealed a weakness in the teaching performance at the student of the teachers, since not a single student reached up to the required performance in all skills; the results also disclosed non-existence of statistically significant differences in the level of teaching performance attributed to differences of specialization and cumulative average except with regard to the axis of evaluation skills where the statistically significant differences at the level (0.001) were in behalf of those with high averages. The study recommended the reconsideration of the educational preparation program at the universities and colleges along with developing the program's courses in a way that could impart the teaching skills to the student of the teachers, thus enabling them to fulfill their future roles, particularly in the field of language lesson planning, implementation, and assessment.
هدفت الدراسة إلى تقويم الأداء التدريسي للطلاب المعلمين المتخصصين في اللغة العربية بكلية التربية بجامعة أم القرى في ضوء المهارات التدريسية، ولتحقيق ذلك استخدم الباحث المنهج الوصفي، وصمم بطاقة ملاحظة تكونت من (58) مهارة في أربعة مجالات تتعلق بتخطيط الدرس اللغوي، وتنفيذه، وتقويمه، والتفاعل وإدارة الصف، قيس صدقها وثباتها، وطبقت على عينة عشوائية مكونة من (30) طالبا معلما من الطلاب المتخصصين في اللغة العربية المنتظمين في كلية التربية ضمن برنامج الإعداد التربوي في العام الدراسي 1438/2017م؛ وقد أسفرت نتائج الدراسة عن وجود ضعف في الأداء التدريسي لدى الطلاب المعلمين، حيث لم يصل أي طالب إلى درجة الأداء المطلوبة في جميع المهارات؛ كما كشفت نتائج الدراسة عن عدم وجود فروق ذات دلالة إحصائية في مستوى الأداء التدريسي تعزى لاختلاف التخصص، والمعدل التراكمي عدا في محور مهارات التقويم حيث وجدت فروق دالة إحصائيا عند مستوى (0.001) لصالح ذوي المعدلات المرتفعة، وقد أوصت الدراسة بإعادة النظر في برنامج الإعداد التربوي في الجامعات والكليات، وتطوير مقرراته؛ بما يسهم في إمداد الطلاب المعلمين بالمهارات التدريسية اللازمة، التي تمكنهم من أداء أدوارهم المستقبلية، لاسيما في مجال تخطيط الدروس اللغوية، وتنفيذها، وتقويمها.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- المهارات التعليمية -- المهارات التدريسية -- الاداء التدريسي -- اللغة العربية -- التعليم الجامعي -- طلاب الجامعات -- جامعة أم القرى -- السعودية -- المدينة المنورة -- مستخلصات الأبحاث